A Study of Research Priority Setting For Myelodysplastic Syndromes In Canada - Christou, Grace (Université d'Ottawa / University of Ottawa, 2022)
The James Lind Alliance approach is a widely used method for research priority setting, yet comprehensive reviews of its implementation are lacking. This thesis therefore focused on reviewing and analyzing the barriers and facilitators to its implementation and on carrying out the early stages of our own priority setting partnership to prioritize research in myelodysplastic syndromes (MDS). A scoping review of the barriers and facilitators encountered when undertaking a James Lind Alliance priority setting partnership was conducted. Our analysis identified that most barriers could be categorized into three main areas: representation, data collection and processing and result useability. We also identified a number of methods that were used successfully to overcome some of the barriers and offered our suggestions for further study. Along with the Aplastic Anemia and Myelodysplasia Association of Canada, we conducted the initial stages of the Canadian MDS Priority Setting Partnership. We were able to collect 206 relevant research questions from people living with MDS, their caregivers and front line health professionals which can be put forward for further prioritization.
Keywords: Prioritization; Patient engagement; James Lind Alliance; MDS